2022
DOI: 10.1021/acsomega.2c01406
|View full text |Cite
|
Sign up to set email alerts
|

Antiamnesic Potential of Malvidin on Aluminum Chloride Activated by the Free Radical Scavenging Property

Abstract: Objectives : Malvidin, a dietary anthocyanin can be a potent drug for the treatment of neuronal toxicity. The investigation was aimed to study the antioxidant role of malvidin against aluminum chloride (AlCl 3 )-induced neurotoxicity in rats. Methods : To evaluate the neuroprotective role of malvidin, the rats were divided into four different groups: group I received saline, group II received AlCl 3 , and groups III and IV were adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…From this study, the effective dose of malvidin can be suggested to range from 100 to 200 mg/kg in oral treatment (Gilani et al, 2022).…”
Section: Plant-derived Anthocyaninsmentioning
confidence: 98%
See 2 more Smart Citations
“…From this study, the effective dose of malvidin can be suggested to range from 100 to 200 mg/kg in oral treatment (Gilani et al, 2022).…”
Section: Plant-derived Anthocyaninsmentioning
confidence: 98%
“…However, the neuroprotective effects of cyanidin in animal models of AD and PD have not reported yet. Another anthocyanin malvidin isolated from mulberries and grapes is reported to ameliorate oxidative stress, neuroinflammation, decrease AChE activity and improve cognitive functions in AD rats (Gilani et al, 2022). From this study, the effective dose of malvidin can be suggested to range from 100 to 200 mg/kg in oral treatment (Gilani et al, 2022).…”
Section: Phyto‐compounds and Their Neuroprotective Effects In Ad And ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The test apparatus comprises of a black ring shaped pool alienated into four quadrants (diameter of 120 cm and a height of 50 cm), filled with 30 cm of water (25±1°C). 37 A 9-cm-diameter immobile black podium was situated 1 cm below the water's surface. Each animal was placed in the water at random, facing the pool's wall.…”
Section: Morris Water Maze (Mwm) Testmentioning
confidence: 99%
“…38,39 A mounted web camera was used during Morris water test training amid 11:00 AM and 2:00 PM to eliminate performance differences in the rats. 37…”
Section: Morris Water Maze (Mwm) Testmentioning
confidence: 99%